Implementation of a Barcode-Based Digital Library System to Enhance Efficiency and Accuracy at MTs NU 01 Pecalungan - Wimara, Nadya Angelica; Wibisono, Iwan Setiawan (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Research Objective. This study aims to develop and implement a barcode-based digital library system at MTs NU 01 Pecalungan to improve service efficiency and data accuracy. Research Method. A sequential explanatory mixed-methods approach was employed, combining quantitative and qualitative data. The quantitative phase compared processing time and data accuracy between manual procedures and the barcode-based system, while user responses were collected through questionnaires involving 82 respondents. Results. The results showed that the barcode-based system significantly improved library service performance, reducing the average loan processing time from 122.4 seconds to 33 seconds and increasing data recording accuracy from 82% to 97%. In addition, most users expressed satisfaction with the system. These findings indicate that the implementation of a barcode-based digital library system effectively enhances the efficiency and accuracy of school library services at MTs NU 01 Pecalungan Keywords: Digital Library, System Development Life Cycle (SDLC), Sequential Explanatory Mixed Methods